Sosialisasi Deteksi Dini dan Terapi Autisme melalui Media Film pada Kader Posyandu Desa dan Kecamatan Padalarang, Kabupaten Bandung Barat - Harras, Kholid Abdullah (Dimasatra, 2024)
Handling autism in Indonesia is still not optimal, especially at the community level. Posyandu cadres have great potential in supporting early detection and intervention of autism, but they often lack adequate training. This article examines a program for socializing early detection and autism therapy conducted through film media for posyandu cadres in the Village and Subdistrict of Padalarang, West Bandung Regency. This training is designed to improve the knowledge and skills of posyandu cadres in recognizing autism symptoms, conducting early detection, and providing appropriate interventions. The methods used include theoretical sessions, educational film screenings, interactive discussions, and practical exercises. Evaluations showed a significant increase in participants' knowledge and skills after the training. Before the training, only 35% of cadres could correctly identify signs of autism, while after the training, this number increased to 88%. Participants also provided positive feedback on the use of film media, which was considered effective in visualizing concepts and real-life scenarios that might be encountered. This program also had a positive impact on the community, with an increase in the number of children detected with autism early and increased public awareness of autism. In conclusion, socialization through film media is an effective method for enhancing the capacity of posyandu cadres in handling autism. This program needs to be replicated in other areas with continuous support to achieve better autism handling in Indonesia.